Facilitating women and removing embarrassment from them in acts of worship Jurisprudence study - Saleh Alshamrani (Journal of Umm Al-Qura University for Shari'ah Sciences and Islamic Studies, 2023)
This paper aims to address the status of women in Islamic law, with the goal of correcting the perceptions held by many intellectuals and others regarding their position in Islam. It also emphasizes the care and respect accorded to women in Islamic law, as well as the removal of any source of embarrassment for them. This study encompasses two main aspects: First: It delves into the fundamental aspect, emphasizing that facilitation and the removal of embarrassment are key objectives of Islamic Sharia in its general provisions, whether related to worship, transactions, marriage, or other areas. Second: It involves the collection of branches where the researcher identifies facilitation and the removal of embarrassment, particularly for women, within Islamic jurisprudence, beyond the scope of worship. This section also includes references to any existing disputes. In total, these branches encompass thirty-five distinct issues.